2006
DOI: 10.1002/bem.20254
|View full text |Cite
|
Sign up to set email alerts
|

No association between occupational exposure to ELF magnetic field and urinary 6‐sulfatoximelatonin in workers

Abstract: A suppression in melatonin secretion is one of the mechanisms proposed to explain the possible adverse effects of extremely low frequency magnetic fields (ELF-MF), but the results of research are inconclusive. This study investigated the effect of occupational ELF-MF exposure on 6-sulfatoximelatonin (6-OHMS). Exposure was monitored for three complete work shifts in 59 workers using personal exposure meters. Environmental exposure was also evaluated. Urinary 6-OHMS in morning samples, an indicator of night-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The latter effect however, has been found in exposure group I (registering minor but not significant difference in melatonin level), which is consistent with the previous findings as well. Other studies reporting no alteration in melatonin concentration (Bortkiewicz et al, 2002;Yellon and Truong, 1998;Gobba et al, 2006) with parallel investigations observing increase or decrease in melatonin levels reflect the inconsistency in this field of investigation. This variation in the interaction of EMF and hence its influence on the living system points towards the complex bio-interaction mechanism and biological sensitivity towards EMF.…”
Section: Discussionmentioning
confidence: 98%
“…The latter effect however, has been found in exposure group I (registering minor but not significant difference in melatonin level), which is consistent with the previous findings as well. Other studies reporting no alteration in melatonin concentration (Bortkiewicz et al, 2002;Yellon and Truong, 1998;Gobba et al, 2006) with parallel investigations observing increase or decrease in melatonin levels reflect the inconsistency in this field of investigation. This variation in the interaction of EMF and hence its influence on the living system points towards the complex bio-interaction mechanism and biological sensitivity towards EMF.…”
Section: Discussionmentioning
confidence: 98%
“…Inhibitory effects of magnetic fields on melatonin production covering a variety of exposure paradigms have been found (19, 4247). There is also a preponderance of negative results (29, 31, 32, 35, 44, 48, 49). This report demonstrated a mild stimulatory effect, which has also been reported (36, 50).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have found no changes in circulatory melatonin after exposure to EMFs (2935). Finally, there have been a few studies where measurable albeit small increases in melatonin either during or after EMF exposure have been reported (36, 50).…”
mentioning
confidence: 99%
“…It should be underlined that a moderate number of epidemiological studies showed no effect of the exposure to ELF-MF on melatonin secretion [33–37]. Gobba et al [33] noted similar levels of 6-sulfatoxymelatonin excretion in two groups of workers exposed to fields ≤0.2  μ T and >0.2  μ T. No association between residential exposure to a 60 Hz magnetic field and 6-sulfatoxymelatonin excretion was observed in adults aged 50–81 years [34].…”
Section: Effects Of Electric Magnetic and Electromagnetic Fieldsmentioning
confidence: 99%
“…Gobba et al [33] noted similar levels of 6-sulfatoxymelatonin excretion in two groups of workers exposed to fields ≤0.2  μ T and >0.2  μ T. No association between residential exposure to a 60 Hz magnetic field and 6-sulfatoxymelatonin excretion was observed in adults aged 50–81 years [34]. Touitou et al [35] showed that the long-term exposure to ELF-MF did not change the level and diurnal secretion of melatonin.…”
Section: Effects Of Electric Magnetic and Electromagnetic Fieldsmentioning
confidence: 99%